Reduced dose to urethra and rectum with the use of variable needle spacing in prostate brachytherapy: a potential role for robotic technology - Vyas, Shilpa; Le, Yi; Zhang, Zhe; Armour, Woody; Song, Daniel Y. (Journal of Contemporary Brachytherapy, 2015)
Purpose: Several robotic delivery systems for prostate brachytherapy are under development or in pre-clinical testing. One of the features of robotic brachytherapy is the ability to vary spacing of needles at non-fixed intervals. This feature may play an important role in prostate brachytherapy, which is traditionally template-based with fixed needle spacing of 0.5 cm. We sought to quantify potential reductions in the dose to urethra and rectum by utilizing variable needle spacing, as compared to fixed needle spacing. Material and methods : Transrectal ultrasound images from 10 patients were used by 3 experienced planners to create 120 treatment plans. Each planner created 4 plan variations per patient with respect to needle positions: 125 I fixed spacing, 125 I variable spacing, 103 Pd fixed spacing, and 103 Pd variable spacing. The primary planning objective was to achieve a prostate V100 of 100% while minimizing dose to urethra and rectum. Results: All plans met the objective of achieving prostate V100 of 100%. Combined results for all plans show statistically significant improvements in all assessed dosimetric variables for urethra (U max , U mean , D 30 , D 5 ) and rectum (R max , R mean , R V100 ) when using variable spacing. The dose reductions for mean and maximum urethra dose using variable spacing had p values of 0.011 and 0.024 with 103 Pd, and 0.007 and 0.029 with 125 I plans. Similarly dose reductions for mean and maximum rectal dose using variable spacing had p values of 0.007 and 0.052 with 103 Pd, and 0.012 and 0.037 with 125 I plans. Conclusions : The variable needle spacing achievable by the use of robotics in prostate brachytherapy allows for reductions in both urethral and rectal planned doses while maintaining prostate dose coverage. Such dosimetric advantages have the potential in translating to significant clinical benefits with the use of robotic brachytherapy.